From sharing voices to making decisions: The case for centring community ownership in evaluation of health programme planning and management. (13th September 2022) - Chi, Chunhuei; Núñez, Alicia; Tuepker, Anaïs
Abstract: Background: Community participation in health programme planning has gained traction in public health in recent decades. When an idea enters the mainstream, it becomes vulnerable to overuse and dilution, and public health professionals claiming "community participation" may intentionally or unintentionally prevent more meaningful participatory action. The principle of community‐centred planning is seldom integrated into programme evaluation. We have previously argued that, to prevent ambiguity and abuse, a stronger and more explicit idea of community ownership is useful. Un‐like "participation", "ownership" leaves little room for dilution. Method: This perspective piece explores a framework to support evaluating community ownership in planning, by emphasising decision‐making power in health planning and management as a necessary element for evaluation alongside other outcomes. After defining the concept of community ownership, we identify and discuss challenges and research gaps related to implementing community ownership in health programme planning, management, and evaluation. Such issues include considering which communities have claims to programme ownership, alternative approaches to representation and participation that support ownership, gathering community values and preferences, and incorporating them into ongoing programme planning, management and evaluation. We consider methodological issues likely to arise when transitioning from gathering community voices ‐ which is valuable but incomplete work ‐ towards community decision making power in planning and evaluation. Results: We use cases from recent policy and research in Chile as examples to consider through the lens of this framework. Finally, we discuss some current constraints in implementing community ownership in healthcare planning and evaluation. Conclusion: We encourage exploring how to practice evaluation in ways that will further our ability to be helpful professional supporters of community self‐determination in finding their paths to health. Highlights: Community ownership is a stronger form of expressing self‐determination. Community ownership can be integrated into programme planning and evaluation. Key challenges to community ownership are defining community members and representations. Approaches by Chile and SIDA are promising steps towards community ownership Perspective.